In-situ growth of porous Cu3(BTC)2 on cellulose nanofibrils for ultra-low dielectric films with high flexibility. (10th June 2022) - Liu, Rui; He, Xiang; Miao, Miao; Cao, Shaomei; Feng, Xin
Highlights: Porous copper-based MOFs were introduced to decrease the polarizability of ANF. In-situ growth of MOFs nanoparticles on cellulose nanofibrils was synthesized. ANF/CNF@CuBTC films were fabricated by a pressured-extrusion procedure. The composite films exhibited excellent mechanical, thermal and dielectric properties. The composite films reached a low dielectric constant lower than 2.2 at 100 MHz. Abstract: The design of flexible polymeric films with internal porous structures has received increasing attention in low dielectric applications. The highly porous metal-organic frameworks (MOFs) of [Cu3 (BTC)2 ] n (BTC=benzene-1, 3, 5-tricarboxylate) were introduced into aramid nanofibers (ANF) matrix by using carboxylated cellulose nanofibrils (CNF) as carriers to obtain strong, flexible, and ultra-low dielectric films. The well-dispersed "flowers-branch" like CNF@CuBTC through in-situ growth of CuBTC on CNF surface endowed the ANF/CNF@CuBTC films with excellent thermal stability, mechanical integrity and low dielectric properties. Besides, the flexible dielectric films exhibited superior ultraviolet (UV) resistance, lower coefficient of thermal expansion (4.28×10 −5 °C − 1 ) and increased water contact angle (83.81°). More interestingly, the removal of guest molecules from the ANF/CNF@CuBTC films according to the vacuum heat treatment (VHT) process significantly improved their dielectric response. The specific surface areas of the composite films after VHT increased obviously, and the dielectric constant and dielectric loss tangent decreased to the expected 1.8–2.2 and 0.001–0.03 at 100 MHz, respectively. Consequently, such designable ultra-low dielectric films with high flexibility play an incredible significance in applications of microelectronics under large deformation conditions, especially in flexible/wearable devices at the arrival of 5 G era.